Compressive Strength and Workability Characteristics of Concrete Mixtures: Kekuatan Tekanan dan Karakteristik Keluwesan Campuran Beton - Rosadi, Rifky; Mulyadi (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Concrete compressive strength and workability are critical parameters in structural engineering and construction quality control. Specific Background: Variations in cement content and water–cement ratio directly determine slump value and compressive strength performance based on standardized laboratory testing. Knowledge Gap: Previous studies have discussed mixture composition and strength development; however, limited discussion is provided regarding systematic comparison of mixture variations under consistent SNI-based testing procedures. Aims: This study aims to analyze the relationship between mixture composition variations and the resulting slump value and compressive strength of concrete specimens. Results: Experimental findings show that differences in cement proportion and water–cement ratio generate measurable changes in workability and compressive strength values, with specific mixture compositions producing higher compressive performance. Slump test results indicate consistent trends corresponding to water content adjustments. Novelty: The study provides structured experimental evaluation using standardized Indonesian National Standards procedures to compare mixture variations within a controlled framework. Implications: The findings contribute practical references for optimizing concrete mixture design in construction practice and support quality control in civil engineering materials testing. Keywords: Concrete Mixture, Compressive Strength, Workability, Water Cement Ratio, Slump Test Key Findings Highlights Mixture proportion variations produce distinct mechanical performance patterns. Cement content differences generate measurable strength deviations. Laboratory testing confirms consistent trends under standardized procedures.